2014
DOI: 10.1039/c3lc51152a
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of flow cytometry with microfluidics and microfabrication

Abstract: A modern flow cytometer can analyze and sort particles on a one by one basis at rates of 50,000 particles per second. Flow cytometers can also measure as many as 17 channels of fluorescence, several angles of scattered light, and other non-optical parameters such as particle impedance. More specialized flow cytometers can provide even greater analysis power, such as single molecule detection, imaging, and full spectral collection, at reduced rates. These capabilities have made flow cytometers an invaluable too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 176 publications
(357 reference statements)
0
147
0
Order By: Relevance
“…29 An additional advantage is that acoustic devices can focus particles across a wide range of applied flow rates and independent of the flow direction, which is not possible in devices that rely on inertial forces for focusing, 28 providing the means to efficiently transport particles or cells for enhanced particle inspection for applications such as flow cytometry and particle sizing. 30,31 The ease of device fabrication and operation can directly allow for the implementation of similar devices for focusing, concentrating, fractionating and sorting objects suspended in fluids. 32 We have shown that the primary radiation forces, which are the strongest forces produced by acoustic standing waves, 1 can focus microparticles flowing through a microfluidic channel at flow rates exceeding 10 ml/hr for a single orifice design.…”
Section: Discussionmentioning
confidence: 99%
“…29 An additional advantage is that acoustic devices can focus particles across a wide range of applied flow rates and independent of the flow direction, which is not possible in devices that rely on inertial forces for focusing, 28 providing the means to efficiently transport particles or cells for enhanced particle inspection for applications such as flow cytometry and particle sizing. 30,31 The ease of device fabrication and operation can directly allow for the implementation of similar devices for focusing, concentrating, fractionating and sorting objects suspended in fluids. 32 We have shown that the primary radiation forces, which are the strongest forces produced by acoustic standing waves, 1 can focus microparticles flowing through a microfluidic channel at flow rates exceeding 10 ml/hr for a single orifice design.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometric systems have been miniaturized through microfluidics and microfabrication (Figure 3) for the detection of various analytes such as red blood cells, CD4+ T cells, natural killer cells, etc. 26,27 . Researchers have also utilized microfluidic flow cytometers for the quantification of bacterial samples from different sources 28 .…”
Section: Microbiology and Cell Biologymentioning
confidence: 99%
“…Flow cytometry analysis, 34 cell-based assays (such as cytotoxicity 35 or induced cellular stress assays 36 ), sorting, manipulation and imaging of single-cells, 37 and cell/tissue engineering, 38,39 are just some of the current applications of microfluidics in biology. Microfluidics also offer the means to create and maintain environments that closely resemble those encountered in vivo.…”
Section: Applications In Biologymentioning
confidence: 99%